Assessment of Bird Species Composition, Relative Abundance, and Distributions in East Gojjam Wetland Habitats, Ethiopia - Gibru, Amare; Biru, Yihew (International Journal of Zoology, 2022)
Many bird species depend on wetlands and the surrounding habitats. However, the status of these wetlands, as well as their biodiversity, is poorly understood and maintained. From January to February 2021, we assessed the compositions, relative abundances, and distributions of bird species throughout five wetland habitats in the East Gojjam zone. In each study site, systematic random sampling techniques were applied at a 4 km interval along the wetland habitats. Bray–Curtis cluster analysis was conducted using PAST software. During the study period, Simpson’s Index and Shannon–Wiener Index were also used to assess the diversity of bird species at various study sites. As a result, a total of 55 bird species from 20 families and 9 orders were identified. During the study period, 49 species were classified as least concern, two were critically endangered species, two were vulnerable species, two were endangered species, and one was an endemic species. During the study, overgrazing and agricultural expansion were identified as threats to biodiversity. To conserve the biological richness of these ecosystems, a wetland conservation strategy and a sustainable usage system are required.